El concepto de crítica en la filosofía política de Gilles Deleuze - Cuamba Herrejón, Juan Cruz (Universidad Michoacana de San Nicolás de Hidalgo, 2014)
This paper addresses the critique concept in political philosophy that could be extracted from the work of Gilles Deleuze. Its pretension is no other one that start a dialogue between some of the theories that have had higher boom in politic philosophy, among which it seeks to break through. Following an old idea which understand the critic as a position or a place from which could settle the limits of a terrain (κρίνω) and from which derive the most diverse senses (delimitation, legislation, perspectives, complaint) the critic becoming in the Deleuze the place of enunciation that has to be constructed every time from which is established the scopes and the limits in the own perspective with the others concomitant and / or discordant. Just that instead of trying to remain pristine and pure the open and created perspective retakes elements of all the theories which differs from. Then, not only are exposed the main concepts that compose the Deleuzean politic philosophy but they offered like alternative to think in a new way the politic and renew the movements of the thought of we who are capable in our time.

El presente trabajo aborda el concepto de crítica en la filosofía política que puede extraerse de la obra de Gilles Deleuze. Su pretensión no es otra que iniciar un diálogo entre algunas de las teorías que mayor auge han tenido en el terreno de la filosofía política, entre las cuales busca abrirse paso. Siguiendo una vieja idea que entiende a la crítica como posicionamiento o lugar a partir del cual pueden establecerse los límites de un terreno (κρίνω) y de la cual derivan los más diversos sentidos (delimitación, legislación, perspectivismo, denuncia), la crítica deviene en Deleuze el lugar de enunciación que tiene que construirse cada vez a partir del cual se establecen los alcances y los límites de la propia perspectiva en relación con otras concomitantes y/o discordantes. Sólo que, en vez de pretender mantenerse prístina y pura, la perspectiva abierta y creada retoma elementos de todas las teorías políticas de las que se distingue. Así́, no sólo son expuestos los principales conceptos que componen la filosofía política deleuzeana sino que se ofrecen como alternativa para pensar de un modo nuevo la política y renovar los movimientos del pensamiento de los que somos capaces en nuestro tiempo.
Instituto de Investigaciones Filosóficas. Facultad de Filosofía. Programa Institucional de Maestría en Filosofía de la Cultura
Keywords: info:eu-repo/classification/cti/4; IIF-M-2014-0048; Critica; Política; Teoría; Gilles Deleuze; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/104